Literature for Language, Language for Literature; Re-visiting the Lang-Lit Relationship in Language Education - Lin, Benedict (SARE: Southeast Asian Review of English, 2017)
In this article I re-visit the relationship between literature and language teaching, in particular to address the question: What exactly is the place and role of literature in language teaching? I also then discuss the role and contribution of the language teacher to literature education. I am concerned with these questions in contexts where language teaching means language education, rather than language training. By the former (language education), I refer to teaching which aims not just at immediate 'practical' uses of the language taught, but more importantly also at broader, more profound understandings of the language, its nature and how it works.